Waist:height ratio: a superior index in estimating cardiovascular risks in Turkish adults. Issue 10 (8th October 2013) - Meseri, Reci; Ucku, Reyhan; Unal, Belgin
Abstract Objective To determine the best anthropometric measurement among waist: height ratio (WHtR), BMI, waist:hip ratio (WHR) and waist circumference (WC) associated with high CHD risk in adults and to define the optimal cut-off point for WHtR. Design Population-based cross-sectional study. Setting Balcova, Izmir, Turkey. Subjects Individuals (n 10 878) who participated in the baseline survey of the Heart of Balcova Project. For each participant, 10-year coronary event risk (Framingham risk score) was calculated using data on age, sex, smoking status, blood pressure, serum lipids and diabetes status. Participants who had risk higher than 10 % were defined as 'medium or high risk'. Results Among the participants, 67·7 % were female, 38·2 % were obese, 24·5 % had high blood pressure, 9·2 % had diabetes, 1·5 % had undiagnosed diabetes (≥126 mg/dl), 22·0 % had high total cholesterol and 45·9 % had low HDL-cholesterol. According to Framingham risk score, 32·7 % of them had a risk score higher than 10 %. Those who had medium or high risk had significantly higher mean BMI, WHtR, WHR and WC compared with those at low risk. According to receiver-operating characteristic curves, WHtR was the best and BMI was the worst indicator of CHD risk for both sexes. For both men and women, 0·55 was the optimal cut-off point for WHtR for CHD risk. Conclusions BMI should not be used alone for evaluating obesity when estimating cardiometabolic risks. WHtR was found to be a successful measurement for determining cardiovascular risks. A cut-off point of '0·5' can be used for categorizing WHtR in order to target people at high CHD risk for preventive actions.